A breakthrough in acute coronary syndrome diagnostics – transdermal troponin assessment - Rejmer, Adrian; Szala-Czerwonka, Karolina; Woś, Natalia; Rojek, Katarzyna; Bednarz, Lucjan; Wijas, Karolina; Bialic, Kinga; Bakalarczyk, Rafał; Bialic, Artur; Majewski, Paweł (Journal of Education, Health and Sport, 2023)
Introduction and purpose: The measurement of cardiac troponins, besides ECG and basic patient examination, is a vital component of the diagnosis and management of patients with acute coronary syndrome (ACS), including unstable angina (UA), non-ST and ST elevation myocardial infarction (NSTEMI, STEMI). Traditionally cardiac troponins have been measured through blood samples, but a new method of transdermal wrist measurement has emerged as a promising alternative. The potential benefits of transdermal troponin measurement are numerous. First and foremost, the non-invasive nature of the method means that patients can be diagnosed “on the spot” and monitored in real time without the need for repeated blood draws, vastly reducing the time for diagnosis and patient qualification for invasive treatment, percutaneous coronary intervention - PCI, if needed. The coronary syndrome is the number 1 cause of death in developed countries which includes morbidity and mortality. With the invention of transdermal troponin assessment device, we can increase the life expectancy and the quality of life in the group of patients with acute coronary syndrome and most importantly, decrease the total turnaround time of diagnosis and significantly reduce the workload in the emergency department.